E-RECRUİTMENT: A REVIEW OF BIST 100 COMPANIES' RECRUİTMENT METHODS AND TOOLS (Third Sector Social Economic Review, 2022)
The aim of this study is to make an assessment of the e-recruitment policies of businesses operating in Turkey. In this direction, data was collected through an examination of career websites of companies in the BIST 100 Index, in order to determine the methods and tools used by them in e-recruitment. A general evaluation was made with frequency analysis in terms of recruitment methods, search capability, tools used during the application, and privacy/security policy. In addition, a comparison was made in terms of providing information on the subject on the company's main values / vision, privacy / security policy, company culture and social assistance and services, the possibility of using a career website / general purpose employment website, search feature, posting job postings, creating a resume, according to the type of sector in which the companies operate. It is expected that the study will contribute to both researchers and practitioners in terms of revealing the preferred e-recruitment methods and tools in Turkey.
Keywords: human resources management; e-recruitment; recruitment resources; job boards; job seekers.